Estimation of regional irrigation water requirements and water balance in Xinjiang, China during 1995–2017 - Li, Yinbo; Wang, Hongwei; Chen, Yun; Deng, Mingjiang; Li, Qian; Wufu, Adiliai; Wang, Dan; Ma, Ligang (PeerJ, 2020)
Estimating water requirements and water balance for irrigated agricultural areas are important and will facilitate the efficient allocation of water resources for agriculture while minimizing the impact on natural ecosystems in arid regions. Based on the Penman-Monteith formula and GIS technology, the irrigation water requirements (IWR) of three main crops (cotton, corn and wheat) during the growing season were estimated and their spatio-temporal changes over the past 23 years (1995–2017) were analyzed in Xinjiang province, China. Our results indicated a dramatic increase in IWR from 14.12 billion m3 in 1995 to 38.99 billion m3 in 2017 due to the rapid cropland expansion of approximately 2.58 × 104 km2 in this period. Monthly IWR usually peaked in summer from May to July and varied in different basins. From the perspective of crops, cotton was identified to have consumed the largest amount of water, reaching 26.39 billion m3 in 2017, accounting for 67.68% of total water consumption. Spatially, the fastest increasing rate of IWR was Tarim Basin, which was attributable to the increase in water requirement of cotton. By comparing IWR and actual irrigation of Xinjiang in 2014, the amount of water scarcity had reached −15.01 billion m3 (−9.80 billion m3 in Tarim Basin and −6.58 billion m3 in Junggar Basin). The planting areas of three main crops (wheat, corn and cotton) were more sensitive to IWR than rising temperature indicated by our model. This study is of great significance for the scientific allocation of water resources in the irrigated areas of the different prefectures of Xinjiang.
Keywords: Water requirement; Water balance; Irrigation; Junggar Basin; Tarim Basin